Less Information, More Comparison, and Better Performance: Evidence from a Field Experiment - EYRING, HENRY; FERGUSON, PATRICK J.; KOPPERS, SEBASTIAN (Journal of Accounting Research, 2021)
ABSTRACT We use a field experiment in professional sports to compare effects of providing absolute, relative, or both absolute and relative measures in performance reports for employees. Although studies have documented that the provision of these types of measures can benefit performance, theory from economic and accounting literature suggests that it may be optimal for firms to direct employees’ attention to some types of measures by omitting others. In line with this theory, we find that relative performance information alone yields the best performance effects in our setting—that is, that a subset of information (relative performance information) dominates the full information set (absolute and relative performance information together) in boosting performance. In cross‐sectional and survey‐data analyses, we do not find that restricting the number of measures shown per se benefits performance. Rather, we find that restricting the type of measures shown to convey only relative information increases involvement in peer‐performance comparison, benefitting performance. Our findings extend research on weighting of and responses to measures in performance reports.